Analysis Of Village Dau, Dak, And Funds On Inequality Distribution Income And Growth In Indonesia 2015-2018 - Yasin R Ismail; Muhammad Amir Arham; Sri Indriyani S Dai (Jambura Equilibrium Journal, 2019)
This study aims to analyze (1) the effect of DAU on economic growth, (2) the effect of DAK on economic growth, (3) the effect of income distribution inequality on economic growth, (4) the influence of the Village Fund on income distribution inequality, (5) the effect of growth the economy against inequality of income distribution. The data used were sourced from the Ministry of Finance through the Directorate General of Fiscal Balance and the Indonesian Central Statistics Agency during the 2015-2018 period, the unit of analysis was 33 provinces in Indonesia. This study uses a simultaneous equation regression model with the two stage least square (2SLS) regression technique with the Fixed Effect Model (FEM). The results showed that, (1) general allocation funds have a positive and significant effect on economic growth, which means that any increase in general allocation funds will be followed by an increase in economic growth. (2) special allocation funds have a negative and significant effect on economic growth. This means that any increase in special allocation funds will make economic growth decline. (3) income distribution inequality has a negative and significant effect on economic growth, which means that any increase in income distribution inequality can as much as reduce economic growth. (4) the variable of village funds has a negative and not significant effect on the inequality of income distribution, which means that any increase in village funds will make the income distribution inequality decrease. (5) economic growth variable has a negative and significant effect on inequality of income distribution, which means that any increase in economic growth can reduce inequality of income distribution decreases. Keywords: DAU, DAK, Village Funds, Economic Growth, Inequality of Income Distribution.